1989
DOI: 10.1055/s-0038-1651032
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Anti-Factor Xa Level and Clinical Outcome in Patients Receiving Enoxaparine Low Molecular Weight Heparin to Prevent Deep Vein Thrombosis after Hip Replacement

Abstract: SummaryStudies in experimental animals have demonstrated that there is a relationship between levels of low molecular weight (LMW) heparin and both bleeding and inhibition of thrombosis. The relationship between these outcomes and ex vivo anti-factor Xa levels has been examined in 163 patients undergoing total hip replacement who were given prophylaxis once daily with a LMW heparin (enoxaparine). Fifty patients received 60 mg of enoxaparine and 113 received 40 mg, both regimens being administered subcutaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
166
2

Year Published

1991
1991
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(173 citation statements)
references
References 21 publications
5
166
2
Order By: Relevance
“…The PK/ PD analysis showed that enoxaparin clearance is a major prognostic factor for the risk of haemorrhage (both all and major haemorrhagic episodes). These results confirm and extend previous observations based on anti-Xa activities in this population and those in a previous study where enoxaparin was given at a lower dose for the prevention of deep-vein thrombosis after hip replacement [1,11].…”
Section: Discussionsupporting
confidence: 92%
“…The PK/ PD analysis showed that enoxaparin clearance is a major prognostic factor for the risk of haemorrhage (both all and major haemorrhagic episodes). These results confirm and extend previous observations based on anti-Xa activities in this population and those in a previous study where enoxaparin was given at a lower dose for the prevention of deep-vein thrombosis after hip replacement [1,11].…”
Section: Discussionsupporting
confidence: 92%
“…Again, clinical trial results are conflicting about whether a relationship exists between anti-Xa levels and patient outcome. Levine et al [24] reported a highly significant association between anti-Xa levels and rates of venographically confirmed deep vein thrombosis and wound hematomas with LMWH prophylaxis following total hip arthroplasty. Other investigators have noted weaker associations between anti-Xa levels and deep vein thrombosis rates with LMWH prophylaxis following general surgery [19,22], but not for major orthopedic procedures [16,21,23,26].…”
Section: Discussionmentioning
confidence: 99%
“…This is also the case with the new low molecular weight heparins [2,3], although animal ex periments indicate a reduced hemorrhagic potential of low molecular weight heparins as compared to unfractionated heparin [4], The hemorrhagic potential of a heparin prepara tion is not fully expressed by its anti-Xa activ ity [5,6], and the precise mechanism by which heparin induces bleeding is not known [5][6][7][8][9][10], Protamine sulfate has been used to reverse the antihemostatic effects of unfrac tionated heparin [11]. The anti-Xa activity of low molecular weight heparins is, however, only partially neutralized by protamine sul fate [12,13], and cases of unsatisfactory re versal of a low molecular weight heparininduced bleeding in patients have been de scribed [14], Some experimental studies in animals suggest, on the other hand, that prot amine sulfate is an effective antidote to low molecular weight heparins [12,[15][16][17],…”
Section: Introductionmentioning
confidence: 79%